Awareness, Knowledge, Attitude, and Skills of Physicians and Nurses Toward Telemedicine in a Low‐ and Middle‐Income Country: A Cross‐Sectional Study - Fatemeh Dahmardeh Kemmak; Parviz Marouzi; Masoumeh Sarbaz; Seyyedeh Fatemeh Mousavi Baigi; Mostafa Sheykhotayefeh; Khalil Kimiafar (Health Science Reports)
ABSTRACT Background and Aims The aim of this research is to examine the awareness, knowledge, attitude, and skills of physicians and nurses concerning telemedicine in hospitals affiliated with Zabol University of Medical Sciences, Iran. Methods This cross‐sectional study was carried out in 2023 among nurses and physicians employed in hospitals associated with Zabol University of Medical Sciences, Iran, utilizing a proportional stratified random sampling technique. Data collection involved a predesigned questionnaire evaluating attitudes, knowledge, awareness, and skills in telemedicine (AKAS). The questionnaire's English version underwent translation using the WHO's standard forward and backward method. The questionnaire's validity and reliability were then assessed by a panel of experts (Cronbach's α = 0.76). Descriptive and analytical data analysis was conducted using SPSS software. Results Seventy‐two nurses, 22 specialist physicians, and six general physicians participated in this research (response rate: 100%). The majority of participants (39%) demonstrated a high level of knowledge about telemedicine, while 44% had low awareness, 48% exhibited a negative attitude, and 45% showed low skills in telemedicine. The findings revealed that educational level significantly predicted participants' knowledge (p < 0.05). Furthermore, participants' awareness levels varied significantly based on educational level, computer literacy, telemedicine training, and willingness to engage in training programs (p < 0.05). Conclusion The physicians and nurses in this study exhibited a considerable level of knowledge about telemedicine. However, their awareness, attitude, and skills regarding telemedicine were found to be lacking. Accordingly, there is a necessity for educational interventions and support for physicians and nurses who are at the forefront of healthcare delivery, as well as the implementation of governmental programs to ensure adequate healthcare services and support for patients in low‐ to middle‐income countries.